Precipitation of Metallic Cations by the Acidic Exopolysaccharides from Bradyrhizobium japonicum and Bradyrhizobium (Chamaecytisus) Strain BGA-1 - Corzo, J. (1994)
The interaction between the acidic exopolysaccharides produced by two Bradyrhizobium strains and several metal cations has been studied. Aqueous solutions in the millimolar range of Fe(3+) but not of Fe(2+) precipitated the exopolysaccharides from Bradyrhizobium (Chamaecytisus) strain BGA-1 and, to a lesser extent, Bradyrhizobium japonicum USDA 110. The precipitation was pH dependent, with a maximum around pH 3. The precipitate was redissolved by changing the pH and by Fe(3+) reduction or chelation. Deacetylation of B. japonicum polysaccharide increased its precipitation by Fe(3+). At pH near neutrality, the polysaccharide from Bradyrhizobium (Chamaecytisus) strain BGA-1 stabilized Fe(3+) solutions, despite the insolubility of Fe(OH)(3). Aluminum precipitated Bradyrhizobium (Chamaecytisus) polysaccharide but not the polysaccharide produced by B. japonicum. The precipitation showed a maximum at about pH 4.8, and the precipitate was redissolved after Al(3+) chelation with EDTA. Precipitation was inhibited by increases in the ionic strength over 10 mM. Bradyrhizobium (Chamaecytisus) polysaccharide was also precipitated by Th(4+), Sn(2+), Mn(2+), and Co(2+). The presence of Fe(3+) increased the exopolysaccharide precipitation by aluminum. No precipitation, gelation, or increase in turbidity of polysaccharide solutions occurred when K(+), Na(+), Ca(2+), Mg(2+), Cu(2+), Cd(2+), Pb(2+), Zn(2+), Hg(2+), or U(6+) was added at several pH values. The results suggest that the precipitation is based on the interaction between carboxylate groups from different polysaccharide chains and the partially hydrolyzed aquoions of Fe(3+), Al(3+), Th(4+), and Sn(2+).